Praktik Etnomedisin dalam Manuskrip Obat-Obatan Tradisional Melayu - Junaidi Junaidi (Manuskripta, 2016)
The practice of ethnomedicine is one of Malay cultural heritage which is very valuable and need to be studied. Various herbs that come from the nature and environment are used in the practice of traditional medicine. One of way to know more about ethnomedicine practice is by studying the manuscript containing the traditional medicine. The practice of ethnomedicine in Malay community had been documented in the form of manuscripts by Raja Haji Ahmad ibni Raja Haji Hasan (Raja Haji Ahmad Physician) on the Bintan island. This study aims to describe herbs, remedies and belief in ethnomedicine practices in the manuscript. This study uses a qualitative method and textual criticism approach. The study found that a variety of herbs that comes from the element of animals and plants are used to cure certain diseases. Various techniques of ethnomedicine are also created in the treatment process. This study concludes that a variety of herbs combining with belief is deemed to have the power to cure any diseases. === Praktik etnomedisin merupakan warisan budaya tradisional Melayu yang sangat berharga dan perlu dipelajari. Berbagai ramuan yang berasal dari alam sekitar digunakan dalam praktek pengobatan tradisional. Salah satu cara untuk mengetahui praktik etno-medisin adalah melalui pengkajian manuskrip tentang obat-obatan tradisional Melayu. Berbagai praktik etnomedisin dalam masyarakat Melayu telah dituliskan oleh Raja Haji Ahmad ibni Raja Haji Hasan (Raja Haji Ahmad Tabib) di Pulau Penyengat. Penelitian ini bertujuan untuk mendeskripsikan ramuan, cara pengobatan, dan kepercayaan dalam praktik etnomedisin yang terkandung dalam manuskrip tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan kritik teks. Hasil penelitian menemukan berbagai ramuan yang berasal dari unsur flora dan fauna digunakan untuk menyembuhkan penyakit tertentu. Berbagai teknik pengobatan juga diciptakan dalam proses pengobatan. Penelitian ini menyimpulkan bahwa berbagai ramuan yang dipadukan dengan kepercayaan dipandang memiliki kekuatan untuk menyembuhkan penyakit.